Isolasi Dan Identifikasi Senyawa Kimia Monoterpen Dari Fraksi Etilasetat Daun Keji Beling (Strobilanthes crispa (L.) Blume) Yang Mempunyai Daya Sitotoksik - Lilik Sulastri; Ristanti Mega Lestari; Partomuan Simanjuntak (Jurnal Fitofarmaka Indonesia, 2021)
Isolation and identification one of chemical compound mono-terpene from Keji beling plant (local name) (Strobilanthes crispa) has been done. Extraction was carried out by maceration of the keji beling leaf powder with ethanol 96%, then partitioned with water-ethyl acetate. Ethylacetate extract was isolated and purified by a cytotoxic guide fractionation system with Brine Shrimp Lethality Test (BSLT) on column chromatography (SiO2; n-hexane - ethylacetate = 20 : 1); and preparative Thin Layer Chromatography (TLC) (SiO2; n-hexane - ethylaseate = 10 : 1) which gave one compound in oily form.  Based on identification by infra red spectra and gas chromatography-mass spectra (GC-MS), the compound is a monoterpene D-limone which has a cytotoxic power of 73,11 ppm.